Configurable and computable instructional model based on gamification elements: a case study on education in software engineering - Raúl Antonio Aguilar Vera; Érika Eunice Briceño Arceo; Julio César Díaz Mendoza; Juan Pablo Ucán Pech (Universidad de Guadalajara, 2020)
This article describes a configurable and computable instructional model based on gamification elements. The empirical evaluation of the model is also reported using the software engineering area as the scope of application; in the experimental study two treatments were compared: the traditional dynamics of using a paper document for the Performance Test, and the use of a Virtual Learning Environment configured based on in the model; the dependent variables considered were time and score. From the statistical analysis it was possible to conclude that the students did not present significant differences in the scores obtained in both treatments; however, the time turned out to be a variable with significant differences.